Westonci.ca is the premier destination for reliable answers to your questions, provided by a community of experts. Join our platform to connect with experts ready to provide precise answers to your questions in different areas. Our platform provides a seamless experience for finding reliable answers from a network of experienced professionals.
Sagot :
To solve the system of equations using the elimination method, we begin with the following equations:
[tex]\[ \begin{array}{l} 2m - 4n = 4 \quad \text{(Equation 1)} \\ m - n = 2 \quad \text{(Equation 2)} \end{array} \][/tex]
We aim to eliminate one of the variables by manipulating and combining these equations. Let's start by isolating one variable. Since the coefficient of [tex]\( m \)[/tex] in Equation 2 is smaller than in Equation 1, it may be easier to work with the second equation. Multiply Equation 2 by 2 so that the coefficients of [tex]\( m \)[/tex] in both equations match:
[tex]\[ 2(m - n) = 2 \cdot 2 \][/tex]
[tex]\[ 2m - 2n = 4 \quad \text{(Equation 3)} \][/tex]
Now we will subtract Equation 3 from Equation 1:
[tex]\[ (2m - 4n) - (2m - 2n) = 4 - 4 \][/tex]
[tex]\[ 2m - 4n - 2m + 2n = 0 \][/tex]
[tex]\[ -2n = 0 \][/tex]
This simplifies to:
[tex]\[ 2n = 0 \][/tex]
[tex]\[ n = 0 \][/tex]
With [tex]\( n \)[/tex] identified as 0, we can substitute [tex]\( n \)[/tex] back into either original equation to solve for [tex]\( m \)[/tex]. Using Equation 2:
[tex]\[ m - n = 2 \][/tex]
[tex]\[ m - 0 = 2 \][/tex]
[tex]\[ m = 2 \][/tex]
Thus, the solution to the system of equations is:
[tex]\[ (m, n) = (2, 0) \][/tex]
Therefore, the correct answer from the given choices is:
[tex]\[ (2,0) \][/tex]
[tex]\[ \begin{array}{l} 2m - 4n = 4 \quad \text{(Equation 1)} \\ m - n = 2 \quad \text{(Equation 2)} \end{array} \][/tex]
We aim to eliminate one of the variables by manipulating and combining these equations. Let's start by isolating one variable. Since the coefficient of [tex]\( m \)[/tex] in Equation 2 is smaller than in Equation 1, it may be easier to work with the second equation. Multiply Equation 2 by 2 so that the coefficients of [tex]\( m \)[/tex] in both equations match:
[tex]\[ 2(m - n) = 2 \cdot 2 \][/tex]
[tex]\[ 2m - 2n = 4 \quad \text{(Equation 3)} \][/tex]
Now we will subtract Equation 3 from Equation 1:
[tex]\[ (2m - 4n) - (2m - 2n) = 4 - 4 \][/tex]
[tex]\[ 2m - 4n - 2m + 2n = 0 \][/tex]
[tex]\[ -2n = 0 \][/tex]
This simplifies to:
[tex]\[ 2n = 0 \][/tex]
[tex]\[ n = 0 \][/tex]
With [tex]\( n \)[/tex] identified as 0, we can substitute [tex]\( n \)[/tex] back into either original equation to solve for [tex]\( m \)[/tex]. Using Equation 2:
[tex]\[ m - n = 2 \][/tex]
[tex]\[ m - 0 = 2 \][/tex]
[tex]\[ m = 2 \][/tex]
Thus, the solution to the system of equations is:
[tex]\[ (m, n) = (2, 0) \][/tex]
Therefore, the correct answer from the given choices is:
[tex]\[ (2,0) \][/tex]
We appreciate your time on our site. Don't hesitate to return whenever you have more questions or need further clarification. Your visit means a lot to us. Don't hesitate to return for more reliable answers to any questions you may have. Thank you for choosing Westonci.ca as your information source. We look forward to your next visit.